Making Keychain Crafts with Asmaul Husna Writing from Wire Feathers: Islamic Art Expression at Elshaddai Studio Klang Kuala Lumpur Malaysia - Hasanah, Nurul; Ritonga, Lia Ariska; Sabariah, Hayatun; Syahfitri, Diani; Salsabila; Arrizka, Aisyah (International Journal of Islamic Thought and Humanities, 2025)
This research examines Indonesian children's training in making feather wire keychain crafts with Asmaul Husna inscriptions at Elshaddai Studio, Klang, Kuala Lumpur, Malaysia. The research also wanted to explore the Islamic meanings and values contained in the work and its impact on the religious understanding and creativity of migrant children. The research method used is a qualitative approach with a case study type, which allows researchers to explore the phenomenon of handicraft skills applied in the social, cultural, and spiritual context of the Indonesian migrant children's community. Data was collected through observation, interview, and documentation techniques. The results showed that the training provided practical skills to the children and introduced them to the values of tawhid and the beauty of Islam through Asmaul Husna. In addition, this training can increase children's self-confidence and provide them with valuable skills in daily life. This keychain craft also has a spiritual function as a reminder of the names of Allah. It could be an effective medium of da'wah to introduce Islamic teachings to the broader community. Thus, this research contributes to Islamic arts-based education among migrant children and introduces the potential of a creative economy through handicrafts.